Pendidikan Karakter Dalam Era Digital: Pengintegrasian Nilai-Nilai Moral Dalam Kurikulum Berbasis Teknologi - Qowim, Agus Nur; Afif, Nur; Mukhtarom, Asrori; Fauziah, Erna (Universitas Muhammadiyah Tangerang, 2024)
Character education has become increasingly crucial in addressing moral challenges in the ever-evolving digital era. This article discusses the approach of integrating moral values into technology-based curricula as a relevant and effective means of shaping students' character. The integration of moral values entails aligning ethical values throughout the curriculum, not treating them as separate subjects. Both teachers and parents play a vital role as role models who exemplify moral behavior to students. They not only teach moral values but also embody them in their daily actions, creating a consistent environment to support students' character development. In addition to traditional classroom learning, this approach encourages practical experiences such as community service, social projects, and extracurricular activities, providing students with opportunities to apply moral values in real-life situations. Continuous evaluation and feedback allow students to monitor their character development. This approach also takes into account cultural contexts and local values, respecting the diversity of moral values worldwide. Integrating moral values into technology-based curricula establishes a strong moral foundation for students to confront moral challenges in the continuously evolving digital world. This article highlights this approach as a relevant and sustainable step in shaping students' character in the digital era. Keywords: Character Education, Digital Era, Moral Values, Integration, Technology-Based Curriculum